Foreign Ownership and Bank Performance: Evidence From Indonesia - Hapsari, Amarilla; Rokhim, Rofikoh (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2017)
The main objective of this study is to examine the impact of foreign entry on the domestic bank-ing markets profitability and overhead costs as financial sector FDI is a relatively new phenom-enon and typically takes the form of banks in industrialized countries establishing branches and facilities in developing countries. A panel data covering the period from 2000 to 2012 is set based on the financial data from 82 commercial banks, which operated in Indonesia as of De-cember 2012 and represented 92 percent of the commercial banks total assets. The results of this study are expected to complement the existing collection of studies on the foreign penetra-tion in the Indonesian banking industry, as to date there has been limited study of the impact of foreign ownership on bank performance in Indonesia. From a policy perspective, this study draws some conclusions which clarify the impacts of foreign penetration on banking industry. The government should continue to open the banking market up to foreign investors if they are proven to bring a positive impact, and should act conversely if they are proven to have an adverse impact on the local banking sector.